Sound Diffusers with Fabric Covering - KAMISIŃSKI, Tadeusz; BRAWATA, Krzysztof; PILCH, Adam; RUBACHA, Jarosław; ZASTAWNIK, Marcin (Archives of Acoustics, 2012)
Fabric covering is often used by designers, as it can easily mask acoustic structures that do not match an interior. However, in the case of sound diffusers based on change in the phase of the reflected wave, the use of fabric covering is not without its effect on acoustics. It reduces the effectiveness of these structures and raises acoustic absorption. In the paper, the authors analyzed the acoustical properties of a selected fabric used to cover sound diffusers. Sound absorption and scattering coefficients for a system composed of sound diffusers and a fabric situated at different distances d were measured. The results were compared to the sound absorption predicted on the basis of Kuttruff’s and Mechel’s theoretical models. Analysis of the results indicates that the fabric has a significant influence on the system’s acoustic parameters. It is also observed, that fabric applied directly on a phase grating diffuser, produces higher absorption than when it is at some distance from it.